2018
DOI: 10.12659/msm.910542
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Phloretin Against Human Gastric Cancer Cell Lines Involves Apoptosis, Cell Cycle Arrest, and Inhibition of Cell Invasion and JNK Signalling Pathway

Abstract: BackgroundGastric cancer is one of most commonly diagnosed cancers and causes significant mortality worldwide. In this study, the antiproliferative and anticancer effects of Phloretin were evaluated against gastric cancer cell lines.Material/MethodsMTT assay was used to assess the proliferation rate of gastric cancer cells. DAPI and annexin V/PI were used for detection of apoptotic cell death. Cell invasion was investigated by Transwell assays and the expression of the proteins was estimated by immunoblotting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Park et al [14] reported that the induction of apoptosis in human colon cancer (HT-29) cells upon treatment with phloretin was associated with increased expression of Bax and release of cytochrome c and Smac/DIABLO in the cytosol, thereby resulting in the cleavage of caspase-8, -9, -7, and -3 and poly(ADP-ribose) polymerase (PARP) [14]. A recent study demonstrated that phloretin induced apoptosis selectively in human gastric cancer cell lines (MGC80-3, BGC-823, SGC-7901, SNU-1, SNU-5, RF-1 and AGS), with IC 50 values ranging from 8 to 32 µM without affecting the growth of normal gastric epithelial cells [39]. Incubation of AGS cells with phloretin reduced the colony formation in a concentration-dependent manner by arresting cell cycle at the G2/M phase.…”
Section: The Biochemistry Behind the Anti-inflammatory And Anti-camentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [14] reported that the induction of apoptosis in human colon cancer (HT-29) cells upon treatment with phloretin was associated with increased expression of Bax and release of cytochrome c and Smac/DIABLO in the cytosol, thereby resulting in the cleavage of caspase-8, -9, -7, and -3 and poly(ADP-ribose) polymerase (PARP) [14]. A recent study demonstrated that phloretin induced apoptosis selectively in human gastric cancer cell lines (MGC80-3, BGC-823, SGC-7901, SNU-1, SNU-5, RF-1 and AGS), with IC 50 values ranging from 8 to 32 µM without affecting the growth of normal gastric epithelial cells [39]. Incubation of AGS cells with phloretin reduced the colony formation in a concentration-dependent manner by arresting cell cycle at the G2/M phase.…”
Section: The Biochemistry Behind the Anti-inflammatory And Anti-camentioning
confidence: 99%
“…Incubation of AGS cells with phloretin reduced the colony formation in a concentration-dependent manner by arresting cell cycle at the G2/M phase. Moreover, the induction of apoptosis in AGS cells by phloretin was associated with the increase in Bax expression, inhibition of Bcl-2 levels and decrease in the phosphorylation of c-Jun N-terminal kinase (JNK) and p38 MAP kinase [39]. In contrast, the activation of JNK and p38 MAP kinase has been attributed to phloretin-induced caspase-3 cleavage in H- ras -transformed human mammary epithelial cells (H- ras -MCF-10A) [55].…”
Section: The Biochemistry Behind the Anti-inflammatory And Anti-camentioning
confidence: 99%
See 1 more Smart Citation
“…Phloretin increased the efficacy of HSP70 penetration and thus its anticancer activity in B16 mouse melanoma cells and K-562 human erythroblasts [27]. Phloretin showed anticancer activity in several human cancer cell lines, including lung (A549), liver (HepG2), colon (HT-29) [28], gastric (AGS) [29], esophageal (EC-109) [30], breast (MDA-MB-231) [31], prostate (LNCaP) [32] and glioblastoma cells [33]. Phloretin has a cancer preventative role by its activity in reducing oxidative DNA damage, as observed in human colon cancer cell lines (Caco-2 and HT-29) [34].…”
Section: Inhibitors Of Glucose Uptakementioning
confidence: 99%
“…Phloretin also has an inhibitory role on dextran sulfate sodium-induced ulcerative colitis in mice by altering nuclear factor-κB, toll-like receptor 4 and PPARγ pathways (16). In addition, phloretin possesses diverse pharmaco-therapeutic effects on human malignancies, including the suppression of oral squamous cell carcinoma by modulating the glucose uptake (17), apoptosis in human gastric cancer by arresting the cell cycle of G2/M phase, suppression of cell invasion by diminution of JNK activity (18), attenuation of triple-negative breast cancer cell proliferation and migration (19) and promote apoptosis in human esophageal cancer (20). A very recent literature suggested that phloretin loaded chitosan nanoparticles augments the mitochondrial mediated intrinsic apoptosis in human oral cancer cells (21).…”
Section: Introductionmentioning
confidence: 99%